KAJIAN SEMANTIK SINONIMITAS KATA FUAD DAN QALB DALAM AL-QUR'AN: ANALISIS DALAM KONTEKS HUBUNGAN MANUSIA DENGAN TUHAN - M. Farid Ridha; Bashori (CV. Adiba Aisha Amira, 2025)
This article analyzes the semantic equivalence of the words Qalb and Fu’ad in the Qur'an and their implications for understanding the relationship between humans and God in Islamic theology. The method used is qualitative with a semantic analysis and exegesis approach on Qur’anic verses containing both terms, supported by exegeses such as Al Misbah, Al Sya'rawi, and others. The results of the study show that Qalb and Fu’ad are not absolute synonyms. Qalb refers to the center of spiritual dynamics that is subject to change (taqallub), functioning as the receptacle for revelation, emotions, and intentions. Meanwhile, Fu’ad denotes a stable inner aspect, serving as the repository of belief (akidah) after undergoing a rational process. The theological implications include: (1) Qalb as a battleground for spiritual struggles that requires the maintenance of purity, (2) Fu’ad as the foundation of steadfast faith, and (3) the interconnection of both forming a holistic relationship between humans and God. In conclusion, this semantic understanding enriches the concept of Islamic spiritual psychology, particularly in tazkiyat al-nafs (purification of the soul) and human accountability before God.